2011
DOI: 10.1073/pnas.1102838108
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic diversity and population structure of the endangered marsupial Sarcophilus harrisii (Tasmanian devil)

Abstract: The Tasmanian devil ( Sarcophilus harrisii ) is threatened with extinction because of a contagious cancer known as Devil Facial Tumor Disease. The inability to mount an immune response and to reject these tumors might be caused by a lack of genetic diversity within a dwindling population. Here we report a whole-genome analysis of two animals originating from extreme northwest and southeast Tasmania, the maximal geographic spread, together with the genome from a tumor taken from one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
193
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(204 citation statements)
references
References 30 publications
8
193
3
Order By: Relevance
“…This could perhaps be mediated by this this species' apparent elevated susceptibility to neoplasia (21,22), low genetic diversity (10,(23)(24)(25), and/or biting behavior (26). However, if this is the case, it is surprising that tumors comparable with DFTD were not reported before 1996 (4,5).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This could perhaps be mediated by this this species' apparent elevated susceptibility to neoplasia (21,22), low genetic diversity (10,(23)(24)(25), and/or biting behavior (26). However, if this is the case, it is surprising that tumors comparable with DFTD were not reported before 1996 (4,5).…”
Section: Discussionmentioning
confidence: 88%
“…Tasmanian devils have low levels of genetic diversity (10,(23)(24)(25), possibly caused by historical population declines driven by past climate change (27). Remaining genetic diversity was possibly further eroded by persecution following European settlement of Tasmania, and, more recently, by the DFTD epidemic (23,27).…”
Section: Discussionmentioning
confidence: 99%
“…CABOG has now been used to assemble the Tasmanian devil genome using a combination of Illumina and 454 reads [39]. The CABOG pipeline will also attempt to construct multiple alelles for regions of sequence variation after contig assembly [40].…”
Section: Next-generation Assemblersmentioning
confidence: 99%
“…SGA was run with only trivial parallelization and could be run serially. No maximum memory requirement was reported for ALLPATHS-LG and so the total memory of the cluster used is given here [31,[36][37][38][39]45]. …”
mentioning
confidence: 99%
“…It has been suggested that the cells monitor and regulate the length of individual telomeres to favor their genomic stability and possibly increased proliferation. 78 Finally, whole genome analysis 44,49 further substantiated the tumor's clonal origin and allograft theory of transmission by demonstrating that DFTs share structural variants and copy number changes distinct from their hosts.…”
Section: Allograft Theory Of Dftd Transmissionmentioning
confidence: 99%